Challenges in the Implementation of Government Budgets; A Case Study of Indonesian Local Governance - Pattiasina, Victor; Noch, Muhamad Yamin; Rumasukun, Mohamad Ridwan; Hijrah, Lailatul; Ikbal, Muhammad; Tamaela, Eduard Yohannis (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
Budget execution stands as a pivotal concern for Indonesian local governments in the present day, holding significance within a specific timeframe. Our study anticipates diverse factors contributing to budget absorption by Indonesian local governments. Through causal research, our objective was to analyze how the independent variables casually influenced the other variables. The study population comprised 34 Indonesian provincial governments across Indonesia. The data were collected from the Regional Financial Management Office of each province, including the Offices, Agencies, Secretariats, and Inspectorates. Employing a purposive sampling technique, we have selected the samples based on specific criteria. Noteworthy regulations along with well-organized and systematic Budget Planning served as the primary driving forces behind government’s budget absorption. Hence, these two factors acted as potent catalysts, promoting optimal budget absorption for developmental pursuit. This alignment reflected the concerted effort to enhance community’s quality of life.